2008
DOI: 10.1016/j.jchemneu.2008.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreactive GnRH type I receptors in the mouse and sheep brain

Abstract: Gonadotropin Releasing Hormone-I (GnRH) has been implicated in an array of functions outside the neuroendocrine reproductive axis. Previous investigations have reported extensive GnRH binding in numerous sites and this has been supported by in situ hybridization studies reporting GnRH receptor mRNA distribution. The present study on mice and sheep supports and extends these earlier investigations by revealing the distribution of cells immunoreactive for the GnRH receptor. In addition to sites previously shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 85 publications
2
31
0
1
Order By: Relevance
“…The hippocampus is central to spatial learning and memory, and Albertson et al (2009) has demonstrated that there are GnRHR type I immunoreactive cells in the CA1 to 4 regions, as well as the dentate gyrus, of the ovine hippocampus. Nuruddin et al (2013b) reported that peripubertal blockade with GnRHa, resulted in sex specific changes in hippocampal (CA1 to 3) mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hippocampus is central to spatial learning and memory, and Albertson et al (2009) has demonstrated that there are GnRHR type I immunoreactive cells in the CA1 to 4 regions, as well as the dentate gyrus, of the ovine hippocampus. Nuruddin et al (2013b) reported that peripubertal blockade with GnRHa, resulted in sex specific changes in hippocampal (CA1 to 3) mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term GnRHa-treatment is therefore used in pediatric human medicine as a co-treatment for conditions such as early onset gender dysphoria, central precocious puberty, idiopathic short stature, growth hormone deficiency, congenital adrenal hyperplasia, and severe hypothyroidism (Carel et al, 2009, Hembree et al, 2009). GnRHR expression and GnRH binding are present in extra-pituitary tissues (Hapgood et al, 2005), including brain regions such as the hippocampus and other limbic structures (Jennes et al, 1997, Albertson et al, 2009, Skinner et al, 2009, Schang et al, 2010). Therefore, long-term GnRHa-treatment may have additional cognitive and behavioral effects, due to a blockade of GnRH signaling outside the HPG axis (Carel et al, 2009, Hembree et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…CNS and the immune system), suggesting the presence of miniature HPG and HPA axis homologs that are able to autonomously regulate local steroidogenesis [15]. GnRH receptors (GnRHRs) have been localized in many regions of the brain such as the hippocampus and cortex and detected in human neuronal cell models like the neuroblastoma SH-SY5Y and M17 cells [16,17]. In M17 cells GnRH induces an up-regulation of the LH␀ subunit [17] and LH mediates neuronal pregnenolone production increasing Steroidogenic Acute Regulatory protein (StAR) expression [18].…”
Section: Introductionmentioning
confidence: 99%
“…It is expressed on the surface of pituitary gonadotrope cells as well as lymphocytes, breast, ovary and prostate (Albertson et al 2008). Genes of hypothalamic pituitary testicular axis plays a key role in male reproductive performance (Huhtaniemi and Alevizaki, 2007).…”
Section: Introductionmentioning
confidence: 99%